Antibacterial and Antifungal Activities of Flueggea anatolica (Euphorbiaceae) - Gemici, Meliha; Demiray, Hatice; Yildirim, Hasan (Asian Journal of Chemistry, 2010)
Flueggea anatolica Gemici (Euphorbiaceae) is a relict endemic shrub remnant from the tertiary period, has been collected from the north of Tarsus (Icel) in Turkey. The antibacterial and antifungal effects of the chloroform extracts of plant leaves were tested against the different bacteria e.g., Echerichia coli ATCC-12228, Salmonella thyphimirium CCM-5445, Proteus vulgaris ATCC 29905, Pseudomonas aeroginosa ATCC-27853, Bacillus subtilis ATCC-6633, Staphylococcus aureus ATCC 6538-P and the yeast Candida albicans ATCC-10239 by micro dilution techniques in vitro. The growth of E. coli , P. aeroginosa and P. vulgaris the Gram-negative bacteria and Candida albicans yeast have been inhibited by the chloroform extract of the leaves of Flueggea anatolica. The extract did not prevent the growth of the other test organisms. This improved the existence of the antibacterial and antifungal activity of the plant. The results showed that leaf extract of F. anatolica had the strong antibacterial and antifungal effect with a minimal inhibitory activity of 0.0025 μg/mL against the E. coli, 0.005 μg/mL against P. aeriginosa bacteria and 0.0025 μg/mL against C. albicans yeast-like fungus used.